Analisis Kuantitas Lemak Pada Keju Yang Tidak Bermerek Yang Diperjualbelikan Di Pasar Terong Kota Makassar - Novianti Novianti; Ardiansah Hasin; Melli Fitriani (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
This research is motivated by the fact that many people consume cheese that is not branded, because it has an affordable price that is in great demand by most Indonesians. The purpose of this study is to find out how much fat in non-branded cheese using the mojonnier method, this research is observational laboratory with the sampling technique using purposive sampling. From the results of examination of quantity of fat as much as 2 cheese samples conducted at the Makassar Health Laboratory Center (BBLK) and analyzed by qualitative tests it can be concluded that there are differences from the two samples where in sample A = 27.80% and in sample B = 18, 19%. The conclusion of this study is that there are differences in the quantity of fat from the two unbranded cheese samples with a low quantity of fat compared to the normal value that has been determined by SNI by 48%.